Communal Territory: Local Agreements for Forest Exploitation in the Indigenous Community of San Juan Pamatácuaro, Mexico - Sandoval-Contreras, Rigoberto (2018)
This article discusses the local agreements that rule and regulate the exploitation of forests in the indigenous community of San Juan Pamatacuaro, state of Michoacan, Mexico. This community enjoys a territory practically covered of a temperate forest, which is divided into two extensions: the plots of land and the area of common use. It is worth mentioning that there are few spaces intended for agricultural use. Community members have the right to a plot for the extraction of timber and so to earn income for the sustenance of the family: this is part of the agreements that make up from a normative system of uses and customs that determine the organization of the territory and the community in aspects such as family, timber work, productive projects, among others. The field work and observations from conceptual framework strengthened the analysis and development of research.